Strengthening Lobbying and Negotiation Skills for Trainees - Fitria Ayuningtyas; Sufian Jusoh; Radita Gora Tayibnapis; Hartanto; Drina Intyaswati; Gustiana Sabarina (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Currently, we are entering an era where high technology and the ability to communicate swiftly are required, such as lobbying and negotiation. Consequently, everyone involved in business must be able to negotiate and lobby at all times. In these conditions, the ability to negotiate and lobby will greatly affect one's career, because the skill to bargain and lobby can benefit both the corporation and the negotiator. Pusat Pelatihan Kerja Daerah Jakarta Selatan (PPKD Jaksel) is a Technical Implementation Unit (UPT) under the DKI Jakarta Manpower and Transmigration Office is in charge of conducting various pieces of training to provide workers with knowledge and skills in the fields of industry, commerce, and various vocations using workshops. PPKD Jaksel captured the importance of lobbying and negotiation in everyday life as well as for business for the trainees. This community service was conducted for 3 (three) days on July 5-7, 2023, at PPKD Jaksel, which is located at Jalan Buncit Raya No. 440, Kalibata, Pancoran, Jakarta Selatan 12740. This activity involves 20 trainees from 1st Batch 2023, Graphic Design Training Class. The ability to communicate remains a key factor in creating relationships because it allows one side to interact with another. Communication is separated into three aspects (3V): visual, verbal, and vocal, with visual receiving the most attention, encompassing the entirety of a person's appearance, including gestures, which dominate the perception of the communication.